Advantages of pyruvate-based fluids in preclinical shock resuscitation-A narrative review - Zhou, Fang-Qiang (Frontiers in Physiology, 2022)
This review focuses on the innate beneficial effects of sodium pyruvate-based fluids, including pyruvate in intravenous solutions, oral rehydration solutions and peritoneal dialysis solutions, on shock resuscitation with various animal models relative to current commercial fluids over the last two decades. Due to its superior pharmacological properties, pyruvate effectively sustains cytosolic glycolytic pathways and mitochondrial oxidative phosphorylation by restoration of redox potentials and reactivation of pyruvate dehydrogenase in hypoxia, even anoxia, and diabetes, reversing the Warburg effect and diabetic glucometabolic aberration. Pyruvate has been demonstrated to protect against multiorgan dysfunction and metabolic disturbance in numerous preclinical studies with various pathogenic injuries. The unique features of pyruvate potential clinical benefits encompass to efficiently correct lethal lactic acidosis via metabolically rapid consumption of intracellular [H+] and robustly protect multiorgan metabolism and function, particularly visceral organs in addition to heart and brain, significantly prolonging survival in various animal models. Pyruvate protection of red blood cells function and preservation of the partial pressure of arterial oxygen should be highly concerned in further studies. Pyruvate is much advantageous over the existing anions such as acetate, bicarbonate, chloride and lactate in commercial fluids. Pyruvate-based fluids act as a therapeutic agent without causing iatrogenic resuscitation injury besides being a volume expander, indicating a potential novel generation of resuscitation fluids including crystalloids and colloids. Pyruvate-based fluids have an enormous potential appeal for clinicians who face the ongoing fluid debate to readily select as the first resuscitation fluid. Clinical trials with pyruvate-based fluids in shock resuscitation are urgently warranted.